Preparación del Bloque Esmeralda para explotación de la asociación de desarrollo minero nivel O, de la parroquia Huertas, cantón Zaruma. - Ordóñez Palacios, Ángel Vinicio (2004)
He mineralized district Portovelo - Zaruma, is sufficiently extensive and varied, the same that was discovered and exploited rustically from the time of the Incas, according to available historical data. With this precedent, the first mining company was established in 1878, called "Zaruma Gold Mining Company", initiating mining in a technical and organized way at the time. The most important company operating in the area was the South American Development Company, SADCO, which was set up in 1904 and executed prospecting, development and production on a well-organized scientific-economic basis until the year 1950. When SADCO was liquidated at the end of 1950, the national state purchased all assets, including equipment and machinery. In March 1951, the "Compañía Industrial Minera Asociada S.A" was legally incorporated, or better known by its acronym "CIMA". The same one that directed the technical operations of the sector until the end of the year of 1978. From 1979 onwards, the Ecuadorian government, represented by the General Directorate of Geology and Mines, DGGM, continued to operate on a smaller scale, which later changed its name to become the Ecuadorian Institute of Mining, INEMIN, within the so-called zone Portovelo Project. The reduction of personnel caused by the low production of mineral, brought with it the unemployment of a great number of miners of the CIMA, this had as consequence the invasion of all the prospective lands, even of the same Project Portovelo. In order to legalize and regularize this chaotic situation, in 1985, INEMIN launched a mining contribution plan, assigning legal properties to national or foreign natural or juridical persons and taking into account certain restrictions as regards To the surface and depth of the extraction. Thus, over the years, small miners began to associate to exploit the mining concessions obtained legally and in this way to strengthen themselves financially. In this way, the Apollo family is associated to request in concession the mining area known as Level Zero. The Ecuadorian State grants the mining title for exploitation on August 25, 1990, forming "THE ASSOCIATION OF MINING DEVELOPMENT LEVEL 0", which has been developing the mining activities in this mining area until today.